An assessment of the potential role of the community in enhancing water and sanitation service provision case study of selected communities in Quezon City - Palacio, Pauline Belinda B. (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
Access to water supply and sanitation (WSS) facilities is not only considered as one of the most basic human need, but is also considered a human right. In 2002, the United nations Committee on Economic, Social, and Cultural Rights (UN CESCR) adopted General Comment No. 15 on the right to water, wherein it states that, the human right to water is indispensable for leading a life in human dignity, and is a prerequisite for the realization of other human rights. This reinforce the right of everyone to reliable, reasonably priced, physically accessible, and sufficient water for domestic uses. In Metro manila, the designated utility for WSS service provision was unable to cope with the demand for efficient and quality service. Only 65% of the service area have access to water supply; furthermore, supply was intermittent where only 10% of the service area have access for an average of 16 hours each day (Fabella 2006). For this reason, the privatization of the WSS utility in Metro Manila was impelled by its failure to provide adequate service to the largest urban center in the Philippines. This was acknowledge as the largest water privatization project and would become a model for its kind in the coming decades. Private sector investment and financing through public-private partnership (PPP) for infrastructure development was used as a tool to improve the efficiency and service delivery to its users. It is for these reasons that the research aims to understand the fundamental impacts of the partnership between the government, private sector, and communities in providing improved WSS service in the selected communities in Quezon City. Specifically; the research focused on assessing the potential role of the community in enhancing water and sanitation service provision in the selected communities in Quezon City. From the research's main objective, the research sought to examine the role of the community in ensuring the sustainable operation of the privatized WSS utility. The selected communities include densely populated barangays in Quezon City, which are Barangays Bagong Silangan, Pansol, Payatas, and UP Campus. As a result of the privatized service, the communities in the concession area benefited from: improved access to safe and better quality water; income saving from affordable cost of water per cubic meter; time saving from queuing is now used for income-earning activities; improved health and hygiene practices; and increased participation of women in the community. The privatization of the water quality resulted in the establishment of various forms and levels of partnership. First, the partnership between the public and private, represented by the MWSS and the Maynilad and Manila Water; and second, the partnership between private and community, as represented by the CBOs/associations/ community leaders. The local organizations, as co-owners, partners, and key solution to WSS service provision are granted the localized monitoring responsibility within their communities. Another form of partnership between public and private that emerged include the relationship between the concessionaires and the local government as represented by barangay. Through coordination with the barangay, the households are formally endorsed for piped connection, provision of financial support for the installation, construction of drainage and desludging service is more organized, capacity building, and information and education campaigns are undertaken. The research contributes to the understanding that adequate consideration to the unique nature of communities and soliciting of participation from communities is vital to the success of any development project. More importantly, the cooperation and mobilization of active local organizations as partners assisted in motivating the community members to actively take part in the development initiative.